The Effect of Power Distance, Moral Intensity, and Professional Commitment on Whistleblowing Decisions - Florencia Pangestu; Dian Kartika Rahajeng (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: Whistleblowing decisions are one of the keys in fraud detection. Considering the rise of fraud cases in organizations, this individual action has a significant impact on organizational performance. Therefore, it is necessary to examine factors that influence the whistleblowing decisions of individuals. Background Problems: This study examines the effect of power distance, moral intensity, and professional commitment on the whistleblowing decision of undergraduate accounting students at the Faculty of Economics and Business, Universitas Gadjah Mada (FEB UGM).Novelty: The novelty of our research is we are filling the gap in previous studies by using students as the population; most studies use employees (such as auditors) as the main population. We use students because they form the next fraud-fighting generation to enter the working environment. Therefore, their understanding and perceptions of whistle blowing activities are crucial. This research is considered to be the first micro-level analysis research in the areas. Research Methods: We adopted the survey method and analyzed it using a regression. We use purposive sampling on 189 undergraduate students from the accounting department. Findings/Results: Our findings indicate that power distance, moral intensity, and professional commitment simultaneously affect accounting students’ whistleblowing decisions. Power distance had a negative and significant effect, meanwhile professional commitment had a positive and significant effect and there was no significant effect of moral intensity toward the whistleblowing. Conclusion: Having professional commitment is essential for whistleblowing decision-making. It needs individual awareness and professional ethics, as well as improvements to people’s morals and values.